Spirituality and Transcendental meditation practitioners’ experiences in South Africa and Ghana - Boatsi, Tenneson (Journal of spirituality in mental health, 2025)
Spirituality involves being in harmony with the cosmos or nature and a willingness to engage in good works for the sake of mankind; for instance, love for one another, care for the environment, and the production and protection of the common good for society. Spirituality could also be defined as the connectedness with nature or the cosmos, seeing beyond the circumstances of one’s limitation and the suffering one encounters (transcendence) and understanding one purpose and meaning of one existence. In an African context, spirituality is experienced by many people as being in touch with one’s spirit which is an indication of integration of the body with the spirit and without this spiritual aspect of the essence of oneself, it becomes natural to see and feel problem. When one is permanently established on the platform of the Transcendental Being, life is lived in eternal freedom and enjoyment of blissfulness throughout the day. In this vein, the self silently witnesses daily activity. This is the essence of TM practice where practitioners experience spiritual upliftment. Though much research has been done on TM globally, the spiritual lived experiences of the practitioners have not been adequately explored, especially in South Africa and Ghana. Therefore, the study sought to explore the spiritual lived experiences of TM practitioners in South Africa and Ghana. The study adopted the constructivist paradigm through the lens of phenomenology. In all, 28 participants took part in the study − 14 participants from South Africa and another 14 from Ghana. Open-ended questionnaires and semi-structured interviews were used to collect data for the study. Husserl’s transcendental phenomenological data analysis was used to analyze and synthesize the descriptions of the spiritual lived experiences of the TM practitioners. The results suggest that TM act as a catalyst for the spiritual growth of the participants from both countries and that they experienced spiritual upliftment with the practice of TM. However, two participants both females were of the view that TM has nothing to do with their spirituality. It is the recommendation of this study that people who seek a spiritual path to discover their purpose and meaning in life explore this technique although there are other paths toward spiritual enlightenment. For instance, Christian’s contemplations player and Sufism.